Racism Phenomenon Portrays in Till Movie by Chinonye Chukwu: racism, types of racism, respond to racism - Yusuf, Aprilulloh; Hastuti, Dwi; Pratama, Rizky Mirani Desi (Media Antartika Indonesia, 2023)
This research aims to find what kinds of racism are shown in the Till movie, the amount of racist phenomena that occur in the Till movie, and the black people respond to racism in the Till movie. The writer used qualitative methods with a semiotic approach focusing on language signs of racism. There are two data-collecting techniques: Primary Data and Secondary Data. Primary data is from a video of the Till movie, and secondary data is from the literature review. The writer found six types of racism found in the Till movie. There are Interpersonal Racism, Institutional Racism, Structural Racism, Societal Racism, Discrimination, and Violence. In total, seventeen phenomena of racism occur in the Till movie. There are several black people's responses to the racism they experienced in the Till movie. The reactions are understanding and compassion, community solidarity, celebration, pride in our culture, assistance and guidance of younger generations, advocacy and activism, and support from different races.